Unravelling the molecular mechanism underlying drought stress response in chickpea via integrated multi-omics analysis - Singh, Vikram; Gupta, Khushboo; Singh, Shubhangi; Jain, Mukesh; Garg, Rohini (Frontiers in Plant Science, 2023)
Drought stress affects growth and productivity significantly in chickpea. An integrated multi-omics analysis can provide a better molecular-level understanding of drought stress tolerance. In the present study, comparative transcriptome, proteome and metabolome analyses of two chickpea genotypes with contrasting responses to drought stress, ICC 4958 (drought-tolerant, DT) and ICC 1882 (drought-sensitive, DS), was performed to gain insights into the molecular mechanisms underlying drought stress response/tolerance. Pathway enrichment analysis of differentially abundant transcripts and proteins suggested the involvement of glycolysis/gluconeogenesis, galactose metabolism, and starch and sucrose metabolism in the DT genotype. An integrated multi-omics analysis of transcriptome, proteome and metabolome data revealed co-expressed genes, proteins and metabolites involved in phosphatidylinositol signaling, glutathione metabolism and glycolysis/gluconeogenesis pathways, specifically in the DT genotype under drought. These stress-responsive pathways were coordinately regulated by the differentially abundant transcripts, proteins and metabolites to circumvent the drought stress response/tolerance in the DT genotype. The QTL-hotspot associated genes, proteins and transcription factors may further contribute to improved drought tolerance in the DT genotype. Altogether, the multi-omics approach provided an in-depth understanding of stress-responsive pathways and candidate genes involved in drought tolerance in chickpea.